STRATEGI PENYELESAIAN PERSOALAN PERKALIAN SEDERHANA MELALUI PENDEKATAN GEOMETRI BAGI SISWA SMA YAPIS NIMBOKRANG, JAYAPURA - Ishak Semuel Beno; Felix Reba (JURNAL PENGABDIAN PAPUA, 2021)
The team of the community engagement service chose to use the topic of multiplication in this activity because the classical topic is still a scourge for students at the elementary to intermediate levels. This leads to students' rejection of mathematics learning although there are various methods of counting, such as mencongak, sempoa, kumon and jarimatika. The challenge of creatively critical thinking becomes the main concept in the learning process/ activity development at SMA Yapis Nimbokrang. The learning approach using the geometric method is introduced and applied in solving simple multiplication problems. The data used to measure the success of the method are the results of the pre- and post-tests. Overall there was an increase in the results of the pretest to the posttest, namely 92% of students liked and could understand the use of the geometric method for multiplication. Also, there are about 22% of students who have not used the geometry method optimally although there is a slight increase in the results of their pretest and posttest. Thus, the use of geometric methods in solving simple multiplication problems at SMA Yapis Nimbokrang is considered successful.Keywords: Multiplication; Geometric-Mean; SMA Yapis Nimbokrang